Beyond the SAFE strategy: Systematic review and meta-analysis of prevalence and associated factors of active trachoma among children in Ethiopia - Zufan Alamrie Asmare; Denekew Tenaw Anley; Melaku Ashagrie Belete; Anteneh Mengist Dessie; Melkamu Aderajew Zemene; Ermiyas Alemayehu; Natnael Moges; Natnael Kebede; Sintayehu Simie Tsega; Asaye Alamneh Gebeyehu; Rahel Mulatie Anteneh; Ermias Sisay Chanie (PLoS ONE, 2025)
Background Although the Surgery, Antibiotic, facial cleanliness, and environmental improvement (SAFE) strategy was adopted in Ethiopia over the last five years, there is still a high incidence of trachoma in areas with poor hygiene. In Ethiopia, a systematic review and meta-analysis were conducted before the implementation of SAFE implying, a need for the update. Therefore, this review gives the updated pooled prevalence and associated factors of active trachoma in Ethiopia after the implementation of SAFE. Method The literature search was performed from PubMed, Google Scholar, EMBASE, HINARI, Scopus, and Web of Sciences from January 1–30, 2024. Data were extracted by using a pre-tested and standardized data extraction format and analyzed using STATA 17 statistical software. I2 tests to appraise the heterogeneity across the included studies, a random-effect model to estimate the pooled prevalence, and a sub-group analysis to discern the viable source of heterogeneity were executed. Potential publication bias was also assessed by funnel plot, Egger’s weighted correlation, and Begg’s regression. The odds ratio with its 95% confidence was used to reckon the association between the prevalence and factors. Result From 504 identified studies, 20 articles were included. After the SAFE intervention, the national pooled prevalence of active trachoma among children was 21.16% (95% CI 17.28, 25.04). Fly-eye contact(Adjusted odds ratio (AOR) = 3.83, 95% CI: 2.25, 6.52), facial uncleanliness(AOR = 5.48, 95% CI: 3.02, 9.96), non-utilization of latrine (AOR = 3.30, 95% CI: 2.10, 5.18), and retrieving water from river(AOR = 2.94; 95%CI: 1.42, 6.05) were significantly associated with active trachoma. Conclusion In Ethiopia, the pooled prevalence of active trachoma after SAFE intervention was much higher than the World Health Organization (WHO) threshold prevalence. It continues to pose a significant public health concern and is far from the elimination of trachoma as a public health problem. Fly-eye contact, facial cleanliness, latrine utilization, and source of water increase the odds of active trachoma. Therefore, it is imperative to fine-tune the intervention focus on personal hygiene-related activities in removing dirt, fly-eye contact, and a well-structured approach for both constructing and ensuring the functionality of household taps and latrines. Additionally, It is crucial to initiate a reliable SAFE intervention in Ethiopia.